The Influence of Entrepreneurial Education and Psychological Capital on Entrepreneurial Behavior Among College Students - Cui, Jun (Frontiers in Psychology, 2021)
This research investigated the influence of entrepreneurial education (EE) on entrepreneurial behavior (EB) through psychological capital (PC). A cross-section survey data of 1,405 college students in China were used to test the proposed hypothesis based on human capital theory and PC literature. The research found that EE had direct effects on EB and on all four sub-constructs (hope, self-efficacy, resilience, and optimism) of PC, and that only self-efficacy positively correlated with EB and mediated the relationship between EE and EB while the other three components of PC did not. These findings contribute to the understanding of both educational and psychological effects on EB. The study also has practical implications for policymakers, managers, and educators in entrepreneurial education.